Diabetes Mellitus and Alzheimer’s Disease: The Protection of Epigallocatechin-3-gallate in Streptozotocin Injection-Induced Models - Jia, Jin-Jing; Zeng, Xian-Si; Song, Xin-Qiang; Zhang, Peng-Peng; Chen, Lei (Frontiers in Pharmacology, 2017)
Diabetes mellitus is considered as a risk factor of Alzheimer’sdisease(AD), the front runner of neurodegenerative disorders. Streptozotocin(STZ) is a toxin for pancreatic β-cell, which can construct a model of insulin deficient diabetes through intraperitoneal or intravenous injection. A model generated by intracerebroventricular STZ(icv-STZ) also shows numerous aspects of sporadic AD. The protective roles of tea polyphenols epigallocatechin-3-gallate(EGCG) on both two diseases were researched by some scientists. This review highlights the link between diabetes and AD and recent studies on STZ injection-induced models, and also discusses the protection of EGCG to clarify its treatment in STZ-induced diabetes and AD.